Analyses of the Adsorption Structures of Friction Modifiers by Means of Quantitative Structure-Property Relationship Method and Sum Frequency Generation Spectroscopy - Hiroaki Koshima (Japanese Society of Tribologists, 2010)
Blending an optimum amount of friction modifiers into lubricant is one of the important measures to reduce fuel consumption induced by the frictional loss for automobiles. However, the agents containing metal or phosphorus compounds can cause catalyst poisoning and clogging in the filters of the exhaust gas refining system. Thus, development of metal-free and phosphorus-free agents with a long-term stability under real working condition is highly desirable. In the present work, the friction coefficients on the metal surface in lubricants containing different friction modifiers were investigated by the reciprocating friction test in detail. A statistical method based on the quantitative structure-property relationship (QSPR) analysis has been employed to correlate the chemical nature of additives with their effect on the friction reduction behaviors. An empirical equation relating the molecular structure and its friction reduction efficiency has been proposed as a standard for a good friction modifier. Furthermore, a surface-sensitive vibration spectroscopy, sum frequency generation (SFG) spectroscopy, has been used to analyze the molecular structures of the lubricants adsorbed on the metal surface. The SFG observation suggested that a certain relationship between the adsorption structure and friction reduction effect of these agents.